UAV based remote sensing for developing countries - Kafi, Abdulla Hil; Maisun Ibn Monowar; Antara, Raihana Shams Islam; Maruf, Munir Muhammad (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.